Cardiovascular risk and fitness in veteran football players. Issue 6 (18th March 2016) - Wegmann, M; Steffen, A; Pütz, K; Würtz, N; Such, U; Faude, O; Bohm, P; Meyer, T
ABSTRACT: Veteran football players above 40 years have rarely been subject to scientific investigations. This is worrisome because their number is considerable and their cardiovascular risk probably increased. Therefore, a cross-sectional study was conducted in 100 football players between 40 and 63 years of age. This included a medical history and physical examination, venous blood sampling, measurement of resting blood pressure, a resting electrocardiogram (ECG), an exhaustive cycle ergometry and a multistage field test. Also, measurements of heart rate and blood lactate concentration were carried out during one typical training session and one match. Participants trained 1.0 ± 0.6 sessions per week and played 27 ± 8 matches per season. Of them, 19% were smokers. Resting blood pressure was 138 ± 15/88 ± 8 mmHg. Hypertension prevalence (WHO definition) was 66%. Total cholesterol averaged 220 ± 41 mg . dl −1, HDL 46 ± 13 mg . dl −1 and LDL 134 ± 33 mg . dl −1 . The average 10-year risk for cardiovascular events (Framingham score) was 6%. Mean maximal power output on the cycle ergometer was 2.8 ± 0.6 W . kg −1, mean VO2peak 40.0 ± 7.3 ml . min −1 . kg −1 . Comparing training and competition, no significant differences in cardiovascular and metabolic load were found. In summary, their cardiovascular risk was similar to age-adjusted reference values. However, they showed slightly better ergometric performance. More frequent training stimuli might be necessary to reach more favourable risk factor profiles. Training and competition lead to similar cardiocirculatory and metabolic stress which is considerably high and might put players into danger who have pre-existing cardiac disease.